Выбор допустимых сечений электрических проводов и кабелей в бортовых цепях электрооборудования летательных аппаратов - Баранов, Михаил Иванович (Национальный технический университет "Харьковский политехнический институт", 2020)
Приведены результаты предложенного инженерного электротехнического подхода к расчетному выбору предельно допустимых поперечных сеченийSil электрических неизолированных проводов, изолированных проводов и кабелей с поливинилхлоридной (ПВХ), резиновой (Р) и полиэтиленовой (ПЭТ) изоляцией и медными(алюминиевыми) жилами (оболочками) по условию их термической стойкости, по которым в бортовых силовых цепях электрооборудования летательных аппаратов (ЛА) в аварийном режиме протекает ток ik(t) однофазного короткого замыкания (КЗ) с заданными амплитудно-временными параметрами. На основании этого подхода осуществлен выбор предельно допустимых поперечных сечений Sil для указанных проводов (кабелей) бортовых силовых цепей электрооборудования ЛА с частотой переменного тока f=400 Гц. Выполнена расчетная оценка предельно допустимых амплитуд плотности δilm тока ik(t) указанного КЗ в рассматриваемых проводах и кабелях бортовых силовых цепей ЛА.

Purpose. Implementation of choice of maximum permissible sections Sil of the uninsulated wires and insulated wires (cables) with copper (aluminum) cores (shells) in the on-board power circuits of electrical equipment of different aircrafts with AC current of frequency f>50 Hz. Methodology.Theoretical bases of the electrical engineering, electrophysics bases of technique of high voltage and high pulsed currents, applied thermal physics. Results. The engineering approach is developed for a calculation choice on the condition of thermal resistibility of aircraft cable-conductor products (CCP) of maximum permissible sections Sil of the uninsulated wires,insulated wires and cables with copper (aluminum) cores (shells), polyvinyl chloride (PVC), rubber (R) and polyethylene (PET) insulation, on which in malfunction of operation of on-board aircraft network with AC frequency of f>50 Hz flows of ik(t) current at single phase short circuit (SC) with given amplitude-temporal parameters. It is determined that in the on-boardpower circuits of electrical equipment of aircrafts (f=400 Hz; for permanent time of slump of Ta=3 ms of аperiodic constituent of current of SC) maximum permissible amplitudes ofcurrent density of δilm≈Imk/Sil of single phase SC at time of its disconnecting tkC=5 ms in the on-board network of aircraft without dependence on the numerical value of amplitude Imkof the given current of SC for the uninsulated wires with copper (aluminum) cores is accordingly about 2.48 (1.40) kA/mm2, for wires (cables) with copper (aluminum) cores (shells) and PVC (R) with insulation – 1.85 (1.18) kA/mm2, and for wires (cables) with copper (aluminum) cores (shells) and PET insulation – 1.53 (0.99) kA/mm2. The influence on a choice in the on-board network of aircrafts of maximum permissible sections Sil of its CCP and accordingly maximum permissible amplitudes of current density δilm of current copper (aluminum) parts of its wires and cables of frequency f of AC in the on-board network of aircraft is determined, but duration of flow tkC (time of disconnecting) renders in the on-board network of aircrafts of emergency current of SC ik(t). For diminishing in the on-board power circuits of electrical equipment of aircrafts of maximum permissible sections Sil of the electric wires (cables) applied in them and accordingly providing of decline for different aircrafts of mass and overall indicators of their on-board CCP is needed in the on-boar networks of aircrafts along with the use of enhance frequency of f=400 Hz of AC to apply the fastacting devices of their protecting from SC in course of time wearing-outs of ta<<100 ms. It isshown that application of enhance frequency of f=400 Hz of AC in the on-board networks of aircrafts as compared to its frequency of f=50 Hz results in the considerable increase (in four times) of fastacting of devices of their protection from SC, operation of which is based on the air electric explosion of metallic wire. Originality.First for the on-board network of aircrafts with ACof frequency of f=400 Hz the maximum permissible sections Sil and amplitudes of current density δilm of SC are determined for the uninsulated wires and insulated wires (cables) with copper (aluminum) cores (shells), PVC, R and PET insulation. Practical value.Theobtained re-sults will be used in the increaseof thermal resistibility of CCP with copper (aluminum) cores (shells), PVC, R and PET insula-tion applied in the on-board electricnetworks of different aircrafts.
A choice of acceptable sections of electric wires and cables in on-board circuits of aircraftelectrical equipment
Keywords: частота переменного тока; выбор предельно допустимых сечений кабельно-проводниковой продукции; frequency of alternating current; selection of maximum permissible cross-sections of cable products